PENGARUH POLA MAKAN MASYARAKAT SUKU ALAS TERHADAP STATUS GIZI PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PERAWATAN KUTAMBARU KABUPATEN ACEH TENGGARA - Eliska Eliska (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2017)
ABSTRACT   Hypertension ranks the third of ten serious disease in Aceh Tenggara district.  The condition is probably related to food consumption of the "Alas communities" that tends to have the habit of life such as drinking coffee, smoking, eating fat and salty food. The research was analytic observational with cross sectional study. The population was all Alas people who got medication and medical facility at Kutambaru Health Center. The samples were 59 patients who were affected by hypertension The data were analyzed by using univariate, bivariate, and  multivariate analyses with multiple logistic regression test at the significance level of α=0.05.The result of the research showed that eating pattern in Alas communities ( fat intake) had  influence on the nutritional status (0,023<0.05, OR = 5,148; 95% CI: 1.247-21.253) after were controlled by food requency, energy intake and protein intake.It is recommended that health care providers should provide counseling about eating pattern which  low fat does not take the risk of being affected by overweight.   Key Words : Eating Pattern, Nutritional Status, Hypertension, Alas Community